An Ecclesia and Missio Crucis: Douglas John Hall's Contribution to the Missional Church Conversation. Issue 2 (June 2015) - Peterson, Cheryl M.
Abstract Canadian theologian Douglas John Hall's contextual analysis of the church in North America has contributed significantly to the missional church conversation; however, his own constructive ecclesiology has received less attention. This article presents and critically examines Hall's proposal of a "suffering church" and offers constructive suggestions for further developing it: expanding solidarity into accompaniment; shifting from the category of representation to reconciliation as the paradigm for the church's mission; and finally, considering the theology of the cross in more pneumatological terms.